Clinical challenges in the treatment of incisive molar hypomineralization - Patrícia Ferreira Resende; Carla Oliveira Favretto (Faculdade Meridional IMED, 2019)
Introduction: One of the enamel defects that is a challenge to the pediatric dentists is Molar-Incisive Hipomineralization (HMI), an alteration of systemic origin characterized by a decrease in mineralization from one to four permanent first molars and frequently associated with permanent incisors, which may also be affected. Objective: The purpose of this work is to review the literature on treatment possibilities in molars affected by HMI. Method: Through a bibliographic review, the databases of the Virtual Health Library, Scientific Electronic Library Online (Scielo) and Google Scholar were searched. The terms used were hypomineralization, molar, incisor, anomalies. Results: Treatments range from topical fluoride application to restorations and extractions. The decision of the treatment depends of the degree of affection in the tooth with HMI. The use of fluoride varnishes is essential at the beginning of any treatment the objective is to reduce the sensitivity present in these cases. Conclusions: Through this, it was concluded that, the establishment of a correct plan of treatment is fundamental for the dental element preservation, being necessary the knowledge of this alteration for the professional to make the best choice.